The Diuretic Effect of Yellow Seeded-Watermelon (Citrullus lanatus) Extract in Male White Rats (Rattus norvegicus) - Dyah Tantry Desiana; Muchsin Doewes; Amelya Augusthina Ayusari (Nexus Biomedika, 2015)
Background: Watermelon (Citrullus lanatus) contains flavonoid and pottasium that have diuretic effect. This research aimed to find out the diuretic effect of yellow seeded-watermelon extract on the male white rats (Rattus norvegicus). Methods: This research was a laboratory experimental study using Posttest Only Group Design, done at Laboratory of Setia Budi University Surakarta from November 2014 to January 2015. The research subjects were 30 male white rats of Wistar Strain with age of 3 months old and 200 grams in weight. Samples were taken by purposive sampling. Watermelon was gotten from Jurug Fruit Market Surakarta. Before the treatment, rats were adapted for 5 days and fasted for 18 hours but still provided with drinking water. Yellow seeded-watermelon extract was given orally. The negative control group (KN) was given distilled water 3 ml and the positive control group (KP) was given hydrochlorothiazide 0.3 mg/200 gr of body weight.Test group I (KUI), II (KUII) and III (KUIII), in order,were given yellow seeded-watermelon extract at dose 35 mg, 70 mg and 140 mg per 200 gr of body weight. Rat urine volume was measured every 4 hours for 16 hours. Data were analyzed by Kruskal-Wallis and Mann Whitney test. Results: The average of rat urine volume of KN, KP,KUI, KUII and KUIIIwere 1.247 ml, 5.987 ml, 2.315 ml, 3.357 ml and 4.570 ml, in order. The Mann Whitney test showed there were significant difference among KN, KP, KUI, KUII and KUIII at the first, second and third four hours. Conclusions: Yellow seeded-watermelon (Citrullus lanatus) extract has diuretic effect on the male white rats (Rattus norvegicus). The highest diuretic effect was at dose of 140 mg/200 gr of body weight. Keywords: Citrullus lanatus extract, diuretic effect, hydrochlorothiazide